Quantum dot color conversion film with wrinkle structure and preparation method thereof

By introducing a quasi-period fold structure into the quantum dot color conversion film, the problems of low color conversion efficiency and high energy consumption in the prior art are solved, and high-efficiency light extraction and brightness improvement are achieved, the film thickness is avoided, and the thinness is maintained. .

CN119144109APending Publication Date: 2024-12-17INST OF NEW DISPLAY TECH HENAN ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411054979.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing quantum dot color conversion films have low color conversion efficiency, resulting in low brightness and high energy consumption. The existing methods increase film thickness and manufacturing cost while improving the light extraction efficiency.

Method used

Design and prepare a quantum dot color conversion film with a quasi-periodic fold structure. By forming a quasi-periodic fold structure on the elastomeric film and transferring it to the quantum dot color conversion film using nanoimprinting technology, reducing light loss and improving Light extraction efficiency.

Benefits of technology

Without increasing the film thickness, the light extraction efficiency of the quantum dot color conversion film is improved, achieving higher brightness and lower energy consumption, while maintaining the lightness and thinness characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144109A_ABST
    Figure CN119144109A_ABST
Patent Text Reader

Abstract

The invention discloses a quantum dot color conversion film with a fold structure and a preparation method thereof, and the preparation method specifically comprises the following steps: firstly, preparing a high-grade elastomer film with low Young modulus; placing the thin film in thermal evaporation coating equipment to evaporate metal layers with different thicknesses to obtain an elastomer thin film with a quasi-periodic wrinkle structure, wherein the period of the elastomer thin film is from nanoscale to micron scale; the quantum dot solution and the polymer solution are mixed and stirred to obtain quantum dot-polymer slurry, and the quantum dot-polymer slurry is prepared into a quantum dot-polymer film; and taking the elastomer film with the quasi-periodic wrinkle structure as a template to form a wrinkle pattern on the quantum dot-polymer film through a nanoimprint technology so as to obtain the quantum dot color conversion film with the quasi-periodic wrinkle structure. The period of the prepared quantum dot color conversion film can be regulated and controlled, and the quantum dot color conversion film can reach the micrometer scale from the nanometer scale; at the same time, high light extraction efficiency is achieved without increasing the thickness of the film and maintaining the light and thin characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quantum dot color conversion films, and in particular to a quantum dot color conversion film with a pleated structure and a preparation method thereof. Background Art

[0002] The color conversion film based on quantum dots has great application potential and market prospects in the field of display technology due to its advantages of high color gamut coverage, high color purity, adjustable luminescent color, and high fluorescence quantum yield. The color conversion display application is mainly based on the photoluminescence characteristics of quantum dot materials, which can be divided into incomplete color conversion and complete color conversion. The former is mainly used for the backlight of liquid crystal displays. Under the excitation of blue light LEDs, a white light backlight source is obtained, and then combined with the color filter film inside the liquid crystal display panel to achieve full-color display. In addition, quantum dots can also be used inside liquid crystal display panels as quantum dot filter films, and also with blue light LEDs to achieve full-color display. Complete color conversion uses blue light OLED or blue light LED displays as excitation sources, integrates green and red light quantum dot color conversion layers into the display panel, and adopts color conversion strategies to obtain the required green and red light emissions, which are matched with the blue light OLED or blue light LED itself to achieve full-color display.

[0003] At present, the color conversion efficiency of quantum dot color conversion film is relatively low, resulting in low brightness and high energy consumption. The color conversion efficiency is closely related to the quality of quantum dot materials, the thickness and uniformity of quantum dot films, among which factors such as the size, shape, composition and surface ligands of quantum dots will affect their optical properties and color conversion efficiency, and the thickness of the film will affect the absorption and scattering of light. Chinese invention patent CN 116880093A discloses the introduction of a multi-layer refractive functional layer in the color conversion film layer structure to improve the color conversion efficiency, and Chinese invention patent CN 118073504A discloses the use of metal reflective electrodes and distributed Bragg reflective structures as reflective electrodes of LEDs to enhance light extraction efficiency. Although the methods of the prior art improve the light extraction efficiency, they also increase the thickness of the film and the manufacturing cost. Summary of the invention

[0004] In view of the problems of the prior art, the purpose of the present invention is to provide a quantum dot color conversion film with a quasi-periodic pleated structure and a method for preparing the same. The present invention obtains a quantum dot color conversion film with a quasi-periodic pleated structure through design and preparation. The pleated structure is a quasi-periodic micro-nano structure, which increases the amount of photons escaping from the quantum dot color conversion film and reduces the light loss caused by reflection and refraction, so that the quantum dot color conversion film of the present invention can achieve a higher light extraction efficiency without increasing the film thickness to maintain the thin and light characteristics.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A quantum dot color conversion film, characterized in that the quantum dot color conversion film has a quasi-periodic wrinkled micro-nano structure. The preparation method of the quasi-periodic wrinkled micro-nano structure is not limited to one or more of self-assembly method, photolithography technology, plasma etching, and ultraviolet light irradiation.

[0007] A method for preparing a quantum dot color conversion film with a pleated structure, specifically comprising the following steps: (1) Preparation of an elastomeric film with a quasi-periodic pleated structure: first prepare a high-grade elastomeric film with a low Young's modulus, place the film in a thermal evaporation coating device to evaporate metal layers of different thicknesses to obtain an elastomeric film with a quasi-periodic pleated structure with a period ranging from nanometer scale to micrometer scale. (2) Preparation of a quantum dot color conversion film: mix and stir a quantum dot solution with a polymer solution to obtain a quantum dot@polymer slurry; prepare the slurry into a quantum dot@polymer film; then use the elastomeric film with a quasi-periodic pleated structure prepared in step (1) as a template, and prepare a quantum dot@polymer film with a quasi-periodic pleated structure by nanoimprinting technology, that is, a quantum dot color conversion film with a quasi-periodic pleated structure.

[0008] Preferably, the elastic film with the quasi-periodic wrinkle structure is prepared by using PDMS.

[0009] Preferably, the polymer is selected from one or more of polymethyl methacrylate, polystyrene, polypropylene, polyvinyl chloride, polyethylene, acrylonitrile-butadiene, polycarbonate, polyamides, thermoplastic polyurethanes, low-density polyethylene, high-density polyethylene, polyethylene terephthalate, polyethylene naphthalate, polyphenylene ether, silicone plastic, glass, rubber, and glue.

[0010] Preferably, the polymer is polymethyl methacrylate (PMMA).

[0011] Preferably, the metal includes one of aluminum (Al), titanium (Ti), copper (Cu), nickel (Ni) and gold (Au).

[0012] Preferably, the quantum dots can excite visible light with a wavelength of 460-680nm under irradiation of ultraviolet light of 300-400nm.

[0013] Preferably, the quantum dots include one or more of CdSe / ZnS quantum dots, ZnSe / ZnS quantum dots, InP / ZnS quantum dots, and perovskite quantum dots.

[0014] Preferably, the nanoimprinting conditions are as follows: the imprinting pressure is 10-100 bar, the imprinting temperature is 80-200° C., and the imprinting time is 10-60 s; more preferably: the imprinting pressure is 20 bar, the imprinting temperature is 150° C., and the imprinting time is 30 s.

[0015] The existing technologies mostly use micro-nano structures such as scattering films, nano moth-eye structures, microlens arrays, glass hemispheres, grating structures and nano-pillars to improve the light coupling output efficiency; however, the periodic micro-nano structure has angle dependence, resulting in uneven distribution of luminous intensity. The wrinkle pattern of the present invention is a special quasi-periodic micro-nano structure with a rich Fourier spectrum.

[0016] The beneficial effects of the present invention are:

[0017] The quantum dot color conversion film with a quasi-periodic pleated structure of the present invention has a pleated structure with a rich Fourier spectrum and a wavy cross-section. On the one hand, it can change the direction of light emitted by the quantum dots so that the angle between the emitted light and the normal is less than the critical angle, thereby allowing more photons to escape from the quantum dot color conversion film; on the other hand, it reduces the light loss caused by reflection and refraction, thereby improving the light coupling output efficiency of the quantum dot color conversion film.

[0018] The present invention adopts self-assembly to form a quasi-periodic wrinkle structure, and uses nanoimprinting technology to transfer the wrinkle structure to a quantum dot color conversion film. The technology is simple and convenient. Compared with light extraction microspheres such as polystyrene (PS) nanospheres and mesoporous silica (SiO2) nanospheres embedded in the quantum dot color conversion film, this method can effectively improve the light extraction efficiency without increasing the thickness of the color conversion film.

[0019] The period of the quantum dot color conversion film with a quasi-periodic fold structure prepared by the method of the present invention can be adjusted from nanometer scale to micrometer scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The AFM image (a) and its magnified view and cross-sectional view (b, c) of the quantum dot color conversion film with a small-scale wrinkled structure prepared in an embodiment of the present invention;

[0021] Figure 2 The AFM image (a) and SEM image (b) of the quantum dot color conversion film with a large-scale wrinkled structure prepared in an embodiment of the present invention and its cross section; DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below in conjunction with specific preferred embodiments, but the protection scope of the present invention is not limited thereby. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Unless otherwise defined, all professional terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention; unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0024] A quantum dot color conversion film, characterized in that the quantum dot color conversion film has a quasi-periodic corrugated micro-nano structure; the preparation method of the quasi-periodic corrugated micro-nano structure is not limited to one or more of self-assembly method, photolithography technology, plasma etching, and ultraviolet light irradiation.

[0025] A method for preparing a quantum dot color conversion film with a pleated structure, specifically comprising the following steps: (1) Preparation of an elastomeric film with a quasi-periodic pleated structure: first prepare a high-grade elastomeric film with a low Young's modulus, place the film in a thermal evaporation coating device to evaporate metal layers of different thicknesses to obtain an elastomeric film with a quasi-periodic pleated structure with a period ranging from nanometer scale to micrometer scale. (2) Preparation of a quantum dot color conversion film: mix and stir a quantum dot solution with a polymer solution to obtain a quantum dot@polymer slurry; prepare the slurry into a quantum dot@polymer film; then use the elastomeric film with a quasi-periodic pleated structure prepared in step (1) as a template, and prepare a quantum dot@polymer film with a quasi-periodic pleated structure by nanoimprinting technology, that is, a quantum dot color conversion film with a quasi-periodic pleated structure.

[0026] Preferably, the elastic film with the quasi-periodic wrinkle structure is prepared by using PDMS.

[0027] Preferably, the polymer is selected from one or more of polymethyl methacrylate, polystyrene, polypropylene, polyvinyl chloride, polyethylene, acrylonitrile-butadiene, polycarbonate, polyamides, thermoplastic polyurethanes, low-density polyethylene, high-density polyethylene, polyethylene terephthalate, polyethylene naphthalate, polyphenylene ether, silicone plastic, glass, rubber, and glue; preferably polymethyl methacrylate.

[0028] Preferably, the metal comprises one of aluminum (Al), titanium (Ti), copper (Cu), nickel (Ni) and gold (Au); preferably, it is metal aluminum (Al).

[0029] Preferably, the quantum dots can excite visible light with a wavelength of 460-680nm under irradiation of ultraviolet light of 300-400nm.

[0030] Preferably, the quantum dots include one or more of CdSe / ZnS quantum dots, ZnSe / ZnS quantum dots, InP / ZnS quantum dots, and perovskite quantum dots.

[0031] Preferably, the nanoimprinting conditions are as follows: the imprinting pressure is 10-100 bar, the imprinting temperature is 80-200° C., and the imprinting time is 10-60 s; more preferably: the imprinting pressure is 20 bar, the imprinting temperature is 150° C., and the imprinting time is 30 s.

[0032] Example

[0033] A method for preparing a quantum dot color conversion film with a pleated structure specifically comprises the following steps:

[0034] (1) Preparation of PDMS substrate film: Take an appropriate weight of PDMS main liquid and add it to a beaker. Then, use a rubber-tipped dropper to add the crosslinker to the PDMS main liquid at a mass ratio of 10:1 (PDMS: crosslinker). After stirring evenly, put it into a vacuum drying oven and cast the bubble-free PDMS solution on the glass substrate by spin coating. Subsequently, place the glass substrate containing the PDMS solution in a vacuum drying oven for curing to form a PDMS substrate film.

[0035] (2) Preparation of a wrinkle template: placing the PDMS substrate film in step (1) in a thermal evaporation coating device to evaporate metal layers of different thicknesses to obtain a wrinkle metal layer; uniformly covering the wrinkle metal layer with a PDMS solution containing a curing agent of different mass ratios, and then placing it in a vacuum drying oven, evacuating to the lowest vacuum degree and maintaining it for 12 hours to remove bubbles; finally, maintaining it at 80° C. for 3 hours to complete the curing; finally, peeling off the PDMS wrinkle template after the curing is completed, cleaning it and setting it aside for use;

[0036] (3) Preparation of quantum dot color conversion film: Using 10 mg / mL quantum dot solution, 200 mg / mL PMMA solution was added to the above quantum dot (QDs) solution, and the mixed solution was vigorously stirred at 50°C for 5 h to obtain a uniform QDs-PMMA slurry; the slurry was prepared into a QDs@PMMA film;

[0037] (4) Preparation of a quantum dot color conversion film with a pleated structure: Using the PDMS pleated film prepared in step (2) as a template, a pleated structure is formed on the QDs@PMMA film by nanoimprinting technology to obtain a quantum dot color conversion film with a pleated structure;

[0038] Wherein, the quantum dots are CdSe / ZnS quantum dots; the quantum dot solution and PMMA solution use chloroform as solvent;

[0039] The QDs@PMMA film can be prepared by dripping film evaporation, pulling film formation, coating, spraying, printing, electrospinning, electrophoresis, transfer, atomic layer deposition, rotary spraying and the like, preferably by coating, and most preferably by using an infrared heating belt casting coater: the specific operation is to drop the QDs-PMMA slurry on a glass substrate, the scraper moves automatically, and the slurry is subjected to infrared drying treatment to obtain a color conversion film containing quantum dots; the thickness of the film is controlled by changing the distance between the scraper and the glass substrate.

[0040] The specific operation of the nanoimprinting is as follows: the PDMS wrinkle template prepared in step (2) is attached to the QDs@PMMA film and placed in a nanoimprinter. After the imprinting is completed, the PDMS template is separated from the QDs@PMMA film to obtain a quantum dot color conversion film containing a wrinkle structure.

[0041] The nanoimprinting conditions are preferably: an imprinting pressure of 10-100 bar, an imprinting temperature of 80-200° C., and an imprinting time of 10-60 s; more preferably: an imprinting pressure of 20 bar, an imprinting temperature of 150° C., and an imprinting time of 30 s.

[0042] The metal described in step (2) can be selected from one of aluminum (Al), titanium (Ti), copper (Cu), nickel (Ni) and gold (Au); preferably, it is metal aluminum (Al).

[0043] By controlling the thickness of the coated metal aluminum (Al) in step (2), a quantum dot color conversion film with a quasi-periodic fold structure with a period ranging from nanometer scale to micrometer scale is obtained (Examples 1-10), see Table 1 for details.

[0044] Table 1.

[0045]

[0046] Comparative Example 1

[0047] The method for preparing the quantum dot color conversion film in Comparative Example 1 is substantially the same as that in Example 1, except that the quantum dot color conversion film does not have a quasi-periodic wrinkle structure.

[0048] The light extraction efficiency of the quantum dot color conversion films with different fold periods prepared in the embodiments of the present invention and the comparative examples was tested and calculated, and the calculation results are shown in Table 2. The light extraction efficiency is defined as the ratio of the number of red or green photons emitted by the color conversion film to the number of photons absorbed.

[0049]

[0050] in: is the integrated intensity of the blue band without quantum dots;

[0051] It is the integrated intensity of the red light segment of the red light QDs-PMMA film under the excitation of the blue mini-LED chip;

[0052] It is the integrated intensity of the red light segment of the PMMA film without red QDs under the excitation of the blue mini-LED chip; It is the integrated intensity of the green light segment of the green QDs-PMMA film under the excitation of the blue mini-LED chip;

[0053] It is the integrated intensity of the green light segment of the PMMA film without green QDs under the excitation of the blue mini-LED chip;

[0054] Table 2 Light extraction efficiency of quantum dot color conversion films with different folding periods (%)

[0055]

[0056] It can be seen from Table 2 that compared with the quantum dot color conversion film without a wrinkle structure, the light extraction efficiency of the quantum dot color conversion film with a wrinkle structure of the present invention is significantly improved; and the light extraction efficiency of the quantum dot color conversion film with a wrinkle structure of the present invention for red light is higher than that for green light.

[0057] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A quantum dot color conversion film, characterized in that: The quantum dot color conversion film has a quasi-periodic wrinkled micro-nano structure.

2. The quantum dot color conversion film according to claim 1, characterized in that: The preparation method of the quasi-periodic wrinkled micro-nano structure includes one or more of self-assembly, photolithography, plasma etching, and ultraviolet light irradiation.

3. A method for preparing a quantum dot color conversion film as claimed in claim 1, characterized in that: The specific steps include: (1) Preparation of an elastomeric film with a quasi-periodic wrinkle structure: First, a high-grade elastomeric film with a low Young's modulus is prepared, and the film is placed in a thermal evaporation coating device to evaporate metal layers of different thicknesses to obtain an elastomeric film with a quasi-periodic wrinkle structure with a period ranging from nanometer scale to micrometer scale; (2) Preparation of quantum dot color conversion film: quantum dot solution and polymer solution are mixed and stirred to obtain quantum dot@polymer slurry; the slurry is prepared into quantum dot@polymer film; and then the elastomeric film with quasi-periodic corrugated structure prepared in step (1) is used as a template to prepare quantum dot@polymer film with quasi-periodic corrugated structure by nanoimprinting technology, that is, quantum dot color conversion film with quasi-periodic corrugated structure.

4. The method for preparing a quantum dot color conversion film according to claim 3, characterized in that: The elastic film with the quasi-periodic wrinkle structure is prepared by using PDMS.

5. The method for preparing a quantum dot color conversion film according to claim 3, characterized in that: The polymer is selected from one or more of polymethyl methacrylate, polystyrene, polypropylene, polyvinyl chloride, polyethylene, acrylonitrile-butadiene, polycarbonate, polyamide, thermoplastic polyurethane, low-density polyethylene, high-density polyethylene, polyethylene terephthalate, polyethylene naphthalate, polyphenylene ether, silicone plastic, glass, rubber, and glue.

6. The method for preparing a quantum dot color conversion film according to claim 3, characterized in that: The metal includes one of aluminum (Al), titanium (Ti), copper (Cu), nickel (Ni) and gold (Au).

7. The method for preparing a quantum dot color conversion film according to claim 3, characterized in that: The quantum dots can excite visible light with a wavelength of 460-680nm under the irradiation of ultraviolet light of 300-400nm.

8. The method for preparing a quantum dot color conversion film according to claim 3, characterized in that: The quantum dots include one or more of CdSe / ZnS quantum dots, ZnSe / ZnS quantum dots, InP / ZnS quantum dots, and perovskite quantum dots.

9. The method for preparing a quantum dot color conversion film according to claim 3, characterized in that: The nanoimprinting conditions are specifically as follows: the imprinting pressure is 10-100 bar, the imprinting temperature is 80-200° C., and the imprinting time is 10-60 s.

10. The method for preparing a quantum dot color conversion film according to claim 9, characterized in that: The specific imprinting conditions are: imprinting pressure is 20 bar, imprinting temperature is 150° C., and imprinting time is 30 s.

Citation Information

Cited By

  • Perovskite solar cell with submicroscopic protrusions and preparation method thereof

    CN119730550A